Hubungan Stress Akademik dengan Perilaku Cyberloafing pada Mahasiswa Fakultas Psikologi Universitas Islam Tribakti Lirboyo Kediri - Mentari Marwa; Wahyu Utami; Choerul Bariyah (Journal of Theory and Practice in Islamic Guidance and Counseling, 2025)
Academic stress is a common issue experienced by students and can affect academic performance as well as emotional balance. Cyberloafing behavior, which is the use of the internet for non-academic activities during class or study hours, has drawn the attention of many researchers because it can impact productivity and academic performance. This study aims to determine the relationship between academic stress and cyberloafing behavior among students. From the description above, the research problem can be formulated as follows: What is the relationship between academic stress and cyberloafing behavior among students at the Islamic University of Tribakti Lirboyo Kediri? This research is a correlational quantitative study. The research method used is a survey with a questionnaire to collect data from 30 students. The results of the study indicate that there is a significant positive relationship between academic stress and cyberloafing behavior. The higher the level of academic stress, the higher the cyberloafing behavior exhibited by students. This study concludes that academic stress can be one of the factors influencing cyberloafing behavior among students, and efforts need to be made to reduce academic stress and increase awareness of the negative impacts of cyberloafing.